Kesetaraan Gender pada Film Serial Netflix Gadis Kretek - Ramadhan Putranto; Dyva Claretta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The issue of gender gap and male dominance, which has historically affected the role of women in society, is a common problem. This study aims to examine the representation of gender equality in the Netflix series